PORTRAYING CORONAVIRUS THROUGH METAPHORS IN ONLINE MASS MEDIA HEADLINES - LUKMAN SARJONO, RADEN INDRAJID; BRAM, BARLI (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2021)
Online mass media use metaphors in their headlines to influence the public’s minds. Drawing on Lakoff and Johnson’s (1980) Conceptual Metaphorical Theory on understanding, this paper aimed to explore the Coronavirus through metaphors in three online mass media headlines. A qualitative approach was used to analyze the data. The data, consisting of 30 headlines concerning Coronavirus, were collected from headlines of three online mass media and then classified and mapped based on the Conceptual Metaphorical Theory. The findings showed that 10 types of metaphors were used in 30 headlines. The two most frequent conceptual metaphors of Coronavirus were Coronavirus as War and Coronavirus as Enemy. The metaphors in online mass media headlines can either bring a negative or positive view toward Coronavirus. Metaphors in online mass media headlines can function as a preventive rhetorical tool to educate people about Coronavirus.